O Programa Sinapse da Inovação como fonte de descoberta das vocações inovadoras de uma região: o caso do Espírito Santo - Almeida, Raphael Douglas dos Anjos (2019)
The objective of this dissertation is to analyze if the Program Sinapse da Inovação is a good method for mapping innovative vocations of a region. Using the neoschumpeteriana theoretical framework and contemporary schools of entrepreneurship, the foundations for the study of innovative entrepreneurship were defined and the institutional basis thar this phenomenon uses. It also defined what regional innovative vocations are and the importance of their mapping, as well as why a pre-incubation program is needed. About the Program Sinapse da Inovação, its methodology was analyzed, including the Delta Opportunity method for verifying innovative vocations. Sinapse da Inovação results were verified for executions 4, 5 and 6 in Santa Catarina and the executions of Espírito Santo and Amazonas, by the Delta Opportunity method and by the Setores Portadores do Futuro method. As a result, it has been found that the Program Sinapse da Inovação reliably represents a region's vocations for innovation, as well as helping to deepen the innovation ecosystems of the region in which it is applied, including generating international recognition. The next step of the program is applied nationally in the form of the Centelha The objective of this dissertation is to analyze if the Program Sinapse da Inovação is a good method for mapping innovative vocations of a region. Using the neoschumpeteriana theoretical framework and contemporary schools of entrepreneurship, the foundations for the study of innovative entrepreneurship were defined and the institutional basis thar this phenomenon uses. It also defined what regional innovative vocations are and the importance of their mapping, as well as why a pre-incubation program is needed. About the Program Sinapse da Inovação, its methodology was analyzed, including the Delta Opportunity method for verifying innovative vocations. Sinapse da Inovação results were verified for executions 4, 5 and 6 in Santa Catarina and the executions of Espírito Santo and Amazonas, by the Delta Opportunity method and by the Setores Portadores do Futuro method. As a result, it has been found that the Program Sinapse da Inovação reliably represents a region's vocations for innovation, as well as helping to deepen the innovation ecosystems of the region in which it is applied, including generating international recognition. The next step of the program is applied nationally in the form of the Centelha Program, taking the culture of innovative entrepreneurship to more places in Brazil.